The promise of reason : studies in The new rhetoric - Gage, John T., 1947-; Perelman, Chaïm (Southern Illinois University Press, 2011)
No single work is more responsible for the heightened interest in argumentation and informal reasoning-and their relation to ethics and jurisprudence in the late twentieth century-than Chaïm Perelman and Lucie Olbrechts-Tyteca's monumental study of argumentation, La Nouvelle Rhétorique: Traité de l'Argumentation. Published in 1958 and translated into English as The New Rhetoric in 1969, this influential volume returned the study of reason to classical concepts of rhetoric. In The Promise of Reason: Studies in The New Rhetoric, leading scholars of rhetoric Barbara Warnick, Je.